NILAI-NILAI PENDIDIKAN ISLAM BAGI ANAK USIA DINI DALAM LAGU ISLAMI ANAK USIA DINI - Sumarni sumarni; Musyafa Ali (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2020)
Early childhood learning in KINDERGARTEN or PAUD, there is no doubt that the name plays and sings. The song became one of the media that is often used as a learning media by teachers. There are so many types of song genres in Indonesia, and one of the genre of songs commonly used as a media study in KINDERGARTEN or PAUD is a song with religious genres, with the purpose of planting religious character for children, as a medium for the development of moral religious value for children and others. Ann's research conducted by researchers was classified as a librarary research study by collecting primary and secondary data related to early childhood Islamic songs. This study used a qualitative approach, to interpret and explain the research object, which is the analysis of religious values in early childhood Islamic songs. In this study, researchers took some early childhood Islamic songs as samples, which would later be analyzed what religious values were in the song. The results of this study showed that